2011
DOI: 10.4236/jbise.2011.44037
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy splicing in precursor-mRNA sequences: prediction of aberrant splice-junctions in viral DNA context

Abstract: RNA splicing normally generates stable splice-junction sequences in viruses that are important in the context of virus mimicry. Potential variability in envelop proteins may occur with point-mutations inducing cryptic splice-junctions, which would remain unrecognized by T-memory cells of higher organisms in vaccine trials. Such aberrant splicejunctions result from evolution-specific non-conservation of actual splice-junction sites due to mutations; as such, locations of splice-junctions in a test DNA sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They enable a sequence comparison and offer optimal, (if not sub-optimal), scores on the similarity/dissimilarity between the compared pair of linear sequences (Jones & Pevzer, 2009) Both NW and SW pursuits imply a matrixbased approach with backtracking used to reconstruct the gapped alignments between the sequences being compared; hence, the aligned pair so obtained is assessed for the similarity score as explained earlier. Relevant dynamic programming structures of NW/SW computations are well known in bioinformatics and described widely across an archive of literature (e.g., Arredondo et al, 2005;Needleman & Wunsch, 1970;Neelakanta et al, 2011;Riedel et al, 2008;Smith & Waterman, 1981). In order to understand the basics of NW/SW algorithms, however, relevant pseudocodes are presented in Appendix A and Appendix B with illustrative examples.…”
Section: Results Of a Possible Alignment Done With The Introduction O...mentioning
confidence: 99%
See 1 more Smart Citation
“…They enable a sequence comparison and offer optimal, (if not sub-optimal), scores on the similarity/dissimilarity between the compared pair of linear sequences (Jones & Pevzer, 2009) Both NW and SW pursuits imply a matrixbased approach with backtracking used to reconstruct the gapped alignments between the sequences being compared; hence, the aligned pair so obtained is assessed for the similarity score as explained earlier. Relevant dynamic programming structures of NW/SW computations are well known in bioinformatics and described widely across an archive of literature (e.g., Arredondo et al, 2005;Needleman & Wunsch, 1970;Neelakanta et al, 2011;Riedel et al, 2008;Smith & Waterman, 1981). In order to understand the basics of NW/SW algorithms, however, relevant pseudocodes are presented in Appendix A and Appendix B with illustrative examples.…”
Section: Results Of a Possible Alignment Done With The Introduction O...mentioning
confidence: 99%
“…Notwithstanding the prevalence of such methods, the study addressed in this paper is conceived and motivated by the consideration of finding locally-significant micro-, meso-or macroscopic artifacts in a test image vis-à-vis in a template using a novel binary correlator approach with the underlying correlation exercised via the so-called Needleman-Wunsch (NW) and Smith-Waterman (SW) algorithms. These algorithms are traditionally adopted in bioinformatics (Arredondo et al, 2005;Needleman & Wunsch, 1970;Neelakanta et al, 2011;Riedel et al, 2008;Smith & Waterman, 1981) to compare a pair of 1D-genomic sequences and deduce the "similarity" features between them. The underlying concept thereof is extended here to compare 2D-images and decide their contrasting and comparable details in quantifiable terms using the NW/SW algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The set of synthetic (It is suggested that, in addition to the original descriptions in (Needleman & Wunsch, 1970) and (Smith, & Waterman, 1981). More relevant details on basic and applied considerations of 1D-NW/SW algorithms can be found across an archival of literature (e.g., Attwood & Parry-Smith, 1999;Riedel et al, 2008;Arredondo et al, 2005;Neelakanta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This method also uses nucleotides and stop codons statistics to analyze the DNA sequence. In [24], authors developed a method for prediction of aberrant splicejunctions in viral DNA context. In this work, the sequence of the Dengue type 1 is analyzed in order to demonstrate the pursuit developed in predicting aberrant splice-junctions at cryptic sites in the test sequence.…”
Section: State Of the Artmentioning
confidence: 99%